Regional radiographic damage and functional limitations in patients with ankylosing spondylitis: Differences in early and late disease. Issue 2 (30th January 2013) - Ward, Michael M.; Learch, Thomas J.; Gensler, Lianne S.; Davis, John C.; Reveille, John D.; Weisman, Michael H.
Abstract Objective Both radiographic damage and functional limitations increase with the duration of ankylosing spondylitis (AS). We examined whether radiographic damage contributed more to functional limitations in late AS than in early AS, and if the strength of association varied with the anatomic region of damage. Methods In this cross‐sectional study of 801 patients with AS, we examined associations of the lumbar modified Stoke Ankylosing Spondylitis Spine Score (mSASSS), the cervical mSASSS, lumbar posterior fusion, cervical posterior fusion, and hip arthritis with the Bath Ankylosing Spondylitis Functional Index (BASFI) and the Health Assessment Questionnaire modified for the spondyloarthritides (HAQ‐S). Results Higher lumbar and cervical mSASSS scores were associated with more functional limitations, but there was an interaction between mSASSS scores and the duration of AS, such that the strength of their association with functional limitations decreased with increasing duration of AS. Cervical posterior fusion was associated with worse functioning independent of mSASSS scores. Hip arthritis was significantly associated with functional limitations independent of spinal damage measures. Among patients with AS duration ≥40 years, the number of comorbid conditions accounted for most of the variation in functioning. Results were similar for both the BASFI and the HAQ‐S. Conclusion Although both radiographic damage and functional limitations increase over time in AS, the relative contribution of radiographic damage to functional limitations is lower among patients with longstanding AS than with early AS, suggesting patients may accommodate to limited flexibility. Damage in different skeletal regions impacts functioning over the duration of AS. Functional limitations due to comorbidity supervene in late AS.